Providing UV Protection Features for Woolen Fabric Using Buckthorn Dye - Hüseyin Benli; Muhammedİbrahim Bahtiyari (Journal of Natural Fibers, 2023)
In recent years, many different properties of natural dyestuffs that do not harm the environment and human have been discovered as a result of the search for dyestuffs. Buckthorn based dyes can be considered in this respect, and so they were tested in this study. The berries and leaves of the buckthorn bush trees were used. While dyeing the fabric, along with the dyeing process, other properties that can be added have been investigated. Wool fabrics with no metal salts and with five different metal salts were dyed with natural dye sources at 100°C for 1 hour. After dyeing, all samples were dried at room temperature. Then, the dyed wool samples’ CIE L*a*b* and color efficiency values (K/S) were determined from the obtained colors to show the usability of buckthorn in dyeing. Color fastness to washing, rubbing, perspiration, and light fastness of the samples were also tested, and results were determined in the range of 3–5 points. The T% values between 0.08 and 0.35 for UVA and between 0.09 and 0.18 for UVB were observed in all trials. It has been determined that fabrics treated with buckthorn berries/leaves can provide a protective feature against the harmful rays of the sun.